An energy-based pedestrian accessibility indicator - Sousa, Nuno (2017)
This article presents an approach to pedestrian accessibility based on human effort rather than distance. By measuring effort as the muscular energy required to traverse network arcs with slopes, it is possible to derive an accessibility indicator that takes relief into account. A case study in the city of Coimbra, Portugal, shows that while relief does have a considerable impact on the accessibility thus measured, that impact is global and not local. When accessibility to all types of opportunities are considered, the influence of relief ultimately dilutes due to the geographical scattering of those opportunities.